Social Image and Candidate‘s Image: A Case Study of Voting Behavior in the Gubernatorial Election in Indonesia’s West Java in 2018 (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2020)
This article aims to discuss the behavior of voters in the City of Sukabumi in the Gubernatorial Election of West Java Province in 2018. This research is motivated by the anomaly of the survey results. A pair of candidates who were unseeded before obtained an increase of votes unpredictably. This research focuses on the pattern of behavior of citizens in determining their choices regarding the election. This research applies the cognitive domain model theory to study the pattern of voting behavior. In collecting data, the author distributed questionnaires to 140 respondents chosen from the official voters‘ list. The distribution of sample areas uses stratified random sampling techniques. The author analyzes data by using multinomial logistic regression. This study concludes that social image and candidates‘ images partially become the main consideration in voting behavior. Social image is the only significant factor that influences the voters in deciding their choice. This study concludes that the psychological approach becomes the main basis that underlies the voting behavior of voters and the main identification of the candidate.